Sustainable Physical Resources to Value Co-Creation, Pareto Sales Network, and Marketing Performance - Rianti, Marlia; Muliana; Azis, Emmi; Agustang; Asnur, Widya Wahyuni (Cendekiawan Indonesia Timur, 2023)
This study aims to analyze sustainable physical resources on value co-creation, Pareto sales network, and marketing performance of Bugis silk weaving IKM in Bone Regency. The stages of the research method start from theoretical studies and empirical studies, preparation of proposals, testing the validity and reliability of research instruments, data collection, analysis, and discussion. The data analysis used is a quantitative approach with SEM analysis through data processing assisted by SPSS and SMART PLS. The results of the study show that: 1. Sustainable Physical Resources have a direct effect on Value Co-Creation, 2. Sustainable Physical Resources directly affect the Pareto Sales Network, 3. Sustainable Physical Resources have a direct effect on Marketing Performance, 4. Value Co-Creation has a direct effect on Directly on Marketing Performance, 5. Pareto Sales Network has a direct effect on Marketing Performance, 6. Value Co-Creation mediates the effect of Sustainable Physical Resources on Marketing Performance, 7. Pareto Sales Network mediates the influence of Sustainable Physical Resources on Marketing Performance.